The Relationship Between Parents Attention and Early Childhood Discipline at Kampuang Jambak Kelurahan Batipuh Panjang Kota Padang - Weni Febrianti; Solfema Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research is motivated by the low discipline of children aged 6-7 years in the Jambak Village, Batipuh Panjang District, Padang City, because the children have not been able to control their behavior and have not been able to form their mental or character. The objectives of this study were (1) The lack of parental attention to children's discipline. (2) The lack of willingness of the child to be disciplined. (3) The influence of an unfavorable environment. This research is a correlational study with a quantitative approach. The population in this study were 50 children aged 6-7 years and the sample in this study was taken as much as 75% or consisting of 37 children aged 6-7 years using the Random Sampling method, techniques in data collection using a written statement (questionnaire) and data collection tool in the form of a list of statements. The data analysis technique uses the percentage and product moment formulas. The results of this study indicate that: (1) Parents' attention to children aged 6-7 years in Jambak Village, Batipuh Panjang Village, Padang City is categorized as poor. (2) The discipline of children aged 6-7 years in Jambak Village, Batipuh Panjang Subdistrict, Padang City is categorized as low. (3) There is a significant relationship between parental attention to the discipline of children aged 6-7 years in Jambak Village, Batipuh Panjang Village, Padang City. It is hoped that further researchers will be able to examine new variables so that they can complete the variables in their research.Keywords: Parental Attention, Child Discipline